Pengaruh Konsep Diri Terhadap Stress Mahasiswa Psikologi Universitas Muhammadiyah Gresik - Dias Ade Prasetiyo (Fakultas Psikologi Universitas Teknologi Sumbawa, 2024)
Stress is something that is often encountered and difficult to avoid in daily life. Without tension, existence would lack breath. Anxiety can be tamed through self-perception. This investigation seeks to unravel the impact of self-perception on anxiety levels among students at the Faculty of Psychology, Muhammadiyah University Gresik. The approach applied is quantitative research, where data is gathered via questionnaires based on self-perception and anxiety scales completed by students serving as the study’s sample. Analysis results reveal a positive and meaningful influence between self-perception and anxiety, with a significance level of 0.000 < 0.05 and a correlation coefficient of 0.354. The implications of this research underscore the importance of nurturing a positive self-perception to aid students in managing anxiety, while also opening avenues for further research to explore additional factors impacting the relationship between these two variables.Keywords: Self-Concept, Stress, Students